Upaya Diplomasi Pertahanan ASEAN Di Laut Cina Selatan (ASEAN Defense Diplomacy Efforts in the South China Sea) - Pangemanan, Arcelinocent; Ibrahim, Azmi; Suryanti, Bundhi Tri; Hermansah, Fajar; Putra, Pragyaa Rihesvar Brahma (Jurnal Diplomasi Pertahanan, 2021)
The complexity of the South China Sea issues has sparked overwhelming international attention, whereas overlapping claims between various countries and the presence of external interest result in the instability of the South China Sea itself. When it comes to the South China Sea, its significance as one of the main global trade routes and its nature as a geographically blessed region with an abundant amount of natural resources is certainly inseparable. With that in mind, the presence of the South China Sea is considered a significant advantage for the countries around it, especially ASEAN (Association of Southeast Asian Nations) countries that are now considered as an emerging power in the Asia – Pacific Region. Thus, this research provides a broader understanding of how ASEAN as the epicenter of civilization in the South China Sea could maximize the utilization of its diplomatic corridors, such as the ASEAN Defence Ministers’ Meeting (ADMM) and ADMM Plus as a form of realizing and ensuring stability and security in the region. This is considered a part of an ASEAN effort to establish one of the pillars of ASEAN, which is ASEAN Political-Security Community, in which through ADMM might projects a clear vision of ASEAN to create a more united and cohesive actor regionally and internationally.